Contact Lenses in the Management of Corneal Dystrophies - Farooq, Asim Visal; Colby, Kathryn (Klinische Monatsblätter für Augenheilkunde, 2020)
Among the group of diseases comprising corneal dystrophies, there are a number for which contact lenses may be considered. For example, soft contact lenses may be beneficial in the management of recurrent corneal erosions and advanced bullous keratopathy and may lead to disease attenuation in some conditions. They also may be used in conjunction with surgical procedures to promote tissue healing and patient comfort in the postoperative period. Rigid contact lenses may be beneficial in the setting of irregular astigmatism. The present review of the literature will discuss the use of contact lenses in the management of corneal dystrophies.
Keywords: contact lenses; cornea; experts opinion